KARAKTERUSASI SATUAN KERJA INSTANSI PEMERINTAH UNTUK MENINGKATKAN EFEKTIVITAS PENGELOLAAN KAS MENGGUNAKAN TEKNIK DATA MINING - Febrian, Gilang Fajar; Herutanso, Khamami (JURNAL INFO ARTHA, 2015)
Ther absorption rate of government expenditure in Indonesia is always inconsistent based on data from the Ministry of Finance of Indonesia. The budget absorption rate is always low at the beginning of the year and rose sharply at the end of the fiscal year, especially in the fourth quarter. Some policies arecreated to determine the amount of government expenduiture, such as tge orihected cash needsin the third page of Budget Implementation List (DIPA). However, the policies are still not effectuve enough to determine the real amount of the government’s cast needs. With the current technology, the problems of government’s cash needs can be solved by using the Knowlegde Discovery from Data (KDD) or data mining. Data mining is the process of discovering patterns in large data sets. By utilizing the database of algorithms created 20 clusters that describe the characteristics of the government work unit and spending patterns that can be utilized to improving the effectiveness of government cash management.